Comparation of Pressed Powder Pellet and Fused Glass Bead Preparation Techniques for Mayor Elements Analysis of Rock Samples using X-Ray Fluorescence (XRF) - Asep Rohiman; Agus Saiful Arifin (Indonesian Journal of Physics, 2020)
The composition of chemical elements in rock samples can be used as a tool for classifying rock types, predicting the depositional environment, rock age, and the tectonic environment in which the rock is formed. X-Ray Fluorescence (XRF) is one of the instruments used to analyze rock samples. The advantage of using XRF analysis is that the analysis process can be done more quickly, easily, accurately, and does not damage the sample. However, before measurements are made using the XRF instrument it needs to be supported by an appropriate sample preparation process. In this study, optimal conditions in the standard (CRM) rock sample preparation of GBW 07105 and JR-1 have been studied. The parameters studied were variations in the composition ratio of Cellulose Mycro Crystalin (CMC) with standard (CRM) samples, namely 1: 4 and 1: 3. The technique of mixing the sample is done by using a mortar grinder and a shaker. Optimization of sample preparation was carried out using pressed powder pellet and fused glass bead techniques. Based on the data obtained from the analysis results the best ratio of binders to standard samples is 1: 3. The pressed powder pellet preparation technique is the best technique in analyzing samples using the X-Ray Fluorescence method. Further studies also need to be carried out to analyze minor elements and traces (REEs).